THE INTENTION TO USE E-WALLET DANA ON MILLENNIAL GENERATION IN BANDUNG CITY - Taryana Aditya; Muhardi Muhardi; Nurdin Nurdin (Jurnal Manajemen dan Bisnis Performa, 2025)
The DANA e-wallet is one of several e-wallets experiencing annual user growth in Indonesia. The purpose of this study is to examine how millennials in Bandung, Indonesia, perceive DANA's usability, utility, and trustworthiness to influence their likelihood of using it. Descriptive verification analysis was complemented by quantitative methodology in this study. An online questionnaire was administered as a means of data collection. One hundred millennials living in Bandung who use the DANA e-wallet served as the sample for this study. Based on these findings, the three main criteria for evaluating e-wallets are perceived utility, trustworthiness, and ease of use. However, the level of Intention to Use serves as an excellent indicator. Intention to use is influenced by trust, perceived usefulness, and ease of use simultaneously. A user's intention to use a product is influenced by three factors: trust, perceived usefulness, perceived ease of use, and perceived usefulness. The characteristics of the millennial generation may explain why perceived ease of use has a high value but a small influence on intention to use. Trust is less important than perceived usefulness in determining intention to use.